IMPLIKASI PEMBATALAN KEWENANGAN KOMISI YUDISIAL DALAM PENGAWASAN HAKIM KONSTITUSI TERHADAP PRAKTIK JUDICIAL CORRUPTION - Dwi, Reskiah; Riwanto, Agus (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
This study analyzes and examines the mplications of canceling the authority of the judicial commission under the supervision of constitutional judges on the practice of judicial corruption in Indonesia. This research is a legal research that is of a descriptive analythical, with a legal approach and a conceptual approach. The type of data collected consists of primary legal material and secondary legal material. The data collection technique used is library research. The technical analysis used is a syllogism method that uses a deductive syllogism. The results of the study shows that the cancelling the authority of the judicial commission under the supervision of constitutional judges which is caused by Putusan MK No 005/PUU-IV/2006 and Putusan MK No 1-2/PUU-XII/2014 has caused judicial corruption in the Constitutional Court of republic Indonesia because there is no independent external organ that that can supervise the Constitutional Court Judges.